2016
DOI: 10.1016/j.pmrj.2016.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Falls and Fear of Falling in Ambulatory Persons With Late Effects of Polio

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 37 publications
6
20
0
1
Order By: Relevance
“…Seventy-five percent of the patients reported that they had fallen at least once in the past year, which is similar to the results of previous studies on falls in patients with prior polio (5,9). Other studies (6,8,(10)(11)(12)(13) have reported a fall rate of 59-69% in the same patient group. Regarding falls during the past year, people with prior polio have more than twice as many falls as the general population, 65 years of age and older (14).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Seventy-five percent of the patients reported that they had fallen at least once in the past year, which is similar to the results of previous studies on falls in patients with prior polio (5,9). Other studies (6,8,(10)(11)(12)(13) have reported a fall rate of 59-69% in the same patient group. Regarding falls during the past year, people with prior polio have more than twice as many falls as the general population, 65 years of age and older (14).…”
Section: Discussionsupporting
confidence: 86%
“…A large proportion of the patients experienced fear of falling, as in previous studies (5,8,9) and approximately half of the patients had decreased their walking due to fear of falling. A contributing cause of increased frequency of falls and fear of falling in patients with prior polio may be the increase in slow muscle fibres and a loss of fast muscle fibres (18)(19)(20), which can lead to poorer ability to quickly avoid obstacles when walking.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Similar consequences of fear of falling are described in persons with MS (19), stroke (17) and SCI (18). Previous studies of persons with LEoP have used different versions of the Falls Efficacy Scale (1,5,8,25) to assess fear of falling, and have reported that fear seems to be greatest in activities related to walking. It was also evident here that fear of falling was common during ambulation.…”
Section: Physical and Emotional Consequences Of Fallsmentioning
confidence: 75%
“…It has been shown that reduced muscle strength in the lower limbs (5,8,9), decreased postural control (5,8,15), leg-length discrepancies (9) and walking limitations (1,8) are associated with falls in persons with LEoP. However, this qualitative study has provided a deeper understanding of how impairments following LEoP can affect movement control and walking ability, which makes people more vulnerable to barriers in different surroundings and to seasonal changes.…”
Section: … If I'm Getting Up I Support Myself On a Table And Then I Kmentioning
confidence: 97%